Ronald W. Busuttil, M.D., Ph.D.— TTS 2024 Medawar Prize Laureate - Kupiec-Weglinski, Jerzy W. (Frontiers in Transplantation, 2025)
The Transplantation Society (TTS) has been presenting the Medawar Prize at its biennial Congresses since 1990 in recognition of Sir Peter Medawar's seminal contributions to organ transplantation. This prestigious award acknowledges individuals for their outstanding accomplishments in experimental and clinical transplantation. On September 25, 2024, I was honored to introduce Ronald W. Busuttil, M.D., Ph.D., as the 2024 Medawar Prize Laureate during the 30th TTS Congress in Istanbul, Turkey. This article highlights the remarkable achievements and critical milestones in Dr. Busuttil's over 40-year career in organ transplantation, which have profoundly advanced scientific knowledge and clinical practice, embodying the true spirit of this accolade.